The argonauts - Nelson, Maggie 1973- (Graywolf Press, 2015)
"A genre-bending memoir, a work of 'autotheory' offering fresh, fierce, and timely thinking about desire, identity, and the limitations and possibilities of love and language. At its center is a romance: the story of the author's relationship with the artist Harry Dodge. This story, which includes the author's account of falling in love with Dodge, who is fluidly gendered, as well as her journey to and through a pregnancy, is an intimate portrayal of the complexities and joys of (queer) family-making"...Dust jacket flap